Transcriptional programs that control expression of the autoimmune regulator gene Aire - Herzig, Yonatan; Nevo, Shir; Bornstein, Chamutal; Brezis, Miriam R.; Ben-Hur, Sharon; Shkedy, Aya; Eisenberg-Bord, Michal; Levi, Ben; Delacher, Michael; Goldfarb, Yael; David, Eyal; Weinberger, Leehee; et al. (Nature Immunology, 2017)
Aire is a transcriptional regulator that induces promiscuous expression of thousands of genes encoding tissue-restricted antigens (TRAs) in medullary thymic epithelial cells (mTECs). While the target genes of Aire are well characterized, the transcriptional programs that regulate its own expression have remained elusive. Here we comprehensively analyzed both cis-Acting and trans-Acting regulatory mechanisms and found that the Aire locus was insulated by the global chromatin organizer CTCF and was hypermethylated in cells and tissues that did not express Aire. In mTECs, however, Aire expression was facilitated by concurrent eviction of CTCF, specific demethylation of exon 2 and the proximal promoter, and the coordinated action of several transcription activators, including Irf4, Irf8, Tbx21, Tcf7 and Ctcfl, which acted on mTEC-specific accessible regions in the Aire locus.
CRIS-Team Scopus Importer:2023-03-23